A bibliometric of publication trends in medical image segmentation: quantitative and qualitative analysis - Bahbibi Rahmatullah (Tanjong Malim, 2021)
A bibliometric of publication trends in medical image segmentation: quantitative and qualitative analysis by Bahbibi Rahmatullah